Bile Microbiota in Liver Transplantation: Proof of Concept Using Gene Amplification in a Heterogeneous Clinical Scenario - D'Amico, Francesco; Bertacco, Alessandra; Finotti, Michele; Di Renzo, Chiara; Rodriguez-Davalos, Manuel I.; Gondolesi, Gabriel E.; Cillo, Umberto; Mulligan, David; Geibel, John (Frontiers in Surgery, 2021)
Objective: Historically, bile in the biliary tract has been considered sterile. Most of the series are based on patients with biliary tract diseases or the bile has been obtained with procedures susceptible to contamination. Methods: We evaluated the bile in a heterogeneous cohort of liver donors and recipients patients, with samples obtained in a sterile way, directly from gallbladder and the common bile duct. Results: We assessed the bile microbiota in six liver donors and in six liver recipients after whole or split liver procedures in adult or pediatric recipients. Bile samples were studied using PCR sequencing of the 16S ribosomal RNA gene amplification (rDNA). Conclusions: We demonstrated that the bile is sterile thereby ruling this out as a source of contamination following transplant.